Desain tangki timbun external floating roof kapasitas 75000 MT - Kevin Satria Nugraha; Muhamad Ari; Mochammad Al Amin Karim Al Amin (Journal of Welding Technology, 2020)
Storage tanks are widely used in industry, especially as a storage area for oil and gas mining products. Various types of storage tanks are made based on the pressure, the type of fluid stored and the type of roof used. The roof on the storage tank is divided into a fixed roof, internal floating roof and external floating roof. Floating roof is used as a barrier between the fluid and the empty space in the tank so as to minimize the occurrence of vapor space and the possibility of a fire in the tank. This study discusses the design of an external floating roof storage tank for condensate fluid with a capacity of 75000 metric tons. The design process for the shell course and other parts of the stockpile tank is based on the API 650 standard 12 addendum 2018 edition using the variable design point method. Verification of the results of calculations generated manually is done with finite element software. Manual calculations for the construction of an external floating roof heap tank get the minimum shell plate thickness used is 10 mm. The bottom plate was found to be 8 mm thick. The simulation using finite element software produces the maximum stress values on the shell, shell to bottom, and roof, namely 1.937 MPa, 7,122 MPa, 0.216 MPa, respectively. All stresses that occur are still below the allowable stress of the material. So it can be concluded that the tank construction is still safe